COMPETENCE AND ROLE OF THE ЕUROPEAN CENTRAL BANK IN THE LIGHT OF MODERN CHALLENGES - Ivaz, Mirjana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In the modern world, where economies are constantly facing various challenges, the role and competences of the European Central Bank (ECB) are of key importance for the stability and prosperity of the Eurozone. The ECB has broad competence in the contemporary monetary flows of the Eurozone. Its main responsibilities include: defining and implementing monetary policy, issuing banknotes and coins, banking supervision, foreign exchange operations, maintaining financial stability, economic analysis and research, communication and transparency. These competences enable the ECB to effectively manage monetary flows in the Eurozone and maintain stability and sustainable economic growth in the region. The aim of this paper is to present the regulatory competences of the European Central Bank in the light of contemporary monetary flows.